Marketing science journals - Shrestha, Bharat B (Himalayan Journal of Sciences, 2006)
The wide circulation of a journal is as important as its publication. Himalayan Journal of Sciences 1(2): 71-72, 2003 The full text is of this article is available at the Himalayan Journal of Sciences website